Implementasi Pedagogy Inklusi di SD Negeri Karanganyar Yogyakarta - Galih Rasita Dewi; Hermanto (Universitas Pendidikan Ganesha, 2024)
The general problem of learning opportunities for children with special needs is society's serious problem. Therefore, the quality of inclusive education must always be improved, one of which is the teaching staff (teachers). Every teacher must master and improve various aspects of competence, one of which is the competence used in inclusive education, inclusive pedagogy competence. This research aims to describe the implementation of inclusive pedagogy in schools providing inclusive education. This type of research is descriptive with a qualitative approach via phenomenology. The subjects in this research were one inclusion class teacher and one special supervisor teacher (GPK). The data collection method used was interviewed using an instrument in the form of an interview sheet. The collected data is explained using content analysis techniques to identify the main themes in the news with the application of inclusive pedagogy. The research results show that inclusive pedagogy competence involves the teacher's ability to provide learning that considers student diversity. This is done through efforts to accept, communicate, and build an inclusive environment. By showing the benefits and challenges of implementing inclusive pedagogy, this research can help increase public support for inclusive education.